(untitled) (Archives of Mechanics - Test, 1999)
The aim of this contribution is to apply homogenization methods in order to describe the nonstationary flow of a viscous fluid through a microperiodic porous elastic medium. By using the method of two-scale asymptotic expansions, the macroscopic phenomenological equations describing such a two-phase structure are derived and the formulae for the effective mechanical coefficients are given. The asymptotic approach is justified by the two-scale convergence. It is shown that Darcy’s law is noulocal in time.